A common supersolid skin covering both water and ice - Zhang, Xi (2014)
Consistency in experimental observations, numerical calculations, and theoretical predictions have revealed that the skins of water and ice share the same attribute of supersolidity characterized by an identical H–O vibration frequency of 3450 cm−1. Molecular undercoordination and inter-electron-pair repulsion shortens the H–O bond and lengthens the O:H nonbond, leading to a dual process of nonbonding electron polarization. This relaxation–polarization process enhances the dipole moment, elasticity, viscosity, and thermal stability of these skins with a 25% density loss, which is responsible for the hydrophobicity and toughness of the water skin and results in the slippery behavior of ice.